Peran Moderasi Kepemimpinan Spiritual Pada Hubungan Perilaku Etis, Kualitas Kehidupan Kerja, Kepuasan Kerja Dan Komitmen Organisasi Dosen: Studi Universitas Swasta Islam - Ilham Ilham (Jurnal Sosio Sains, 2022)
The research objectives: to analyze the moderate role of spiritual leadership on the relationship between ethical behavior, quality of work life and job satisfaction on the organizational commitment of lecturers at an Islamic private university. Questionnaires were given to a population of 1,637 lecturers who work at Islamic private universities located in the Higher Education Service Institute Region IX Sultanbatara, with a valid sample of 323 lecturers. After the analysis of normality, validity, and reliability, the overall model meets the test criteria through PLS SEM (partial least square structural equation modeling). The moderate negative role of spiritual leadership on the relationship between ethical behavior and organizational commitment (t = 2,532, p < .05) was statistically supported. It was also found that spiritual leadership had a moderating role in the relationship between quality of work life and organizational commitment (t = 2,962, p < .05). Spiritual leadership as a moderator does not show a moderating effect between job satisfaction and organizational commitment. Tujuan penelitian menganalisis peran moderat kepemimpinan spiritual pada hubungan perilaku etis, kualitas kehidupan kerja dan kepuasan kerja terhadap komitmen organisasi dosen universitas swasta islam. Kuesioner diberikan kepada populasi 1.637 dosen yang bekerja di universitas swasta islam yang berlokasi di Lembaga layanan Pendidikan tinggi wilayah IX Sultanbatara, dengan sampel yang valid adalah 323 dosen. Setelah analisis normalitas, validitas, dan keandalan dinilai model keseluruhan memenuhi kriteria uji melalui PLS SEM (partial least square structural equation modeling). Peran moderat negative kepemimpinan spiritual pada hubungan perilaku etis dan komitmen organisasi (t = 2.532, p <. 05) didukung secara statistik. Juga ditemukan bahwa kepemimpinan spiirutal memiliki peran memoderasi pada hubungan kulaitas kehidupan kerja dan komitmen organisasi (t = 2.962, p < .05). Kepemimpinan spiritual sebagai mederating tidak menunjukkan efek medorat antara kepuasan kerja dan komitmen organisasi.